Técnicas do corpo, mentes religiosas e o cérebro social Observações da antropologia estrutural para a psicologia evolutiva - Lencastre, Marina Prieto Afonso (Trabalhos de Antropologia e Etnologia, 2020)
Traditional religions often dispose of specific body techniques to contact absent realities through trance and hallucinatory activities that are communicated by cultural narration. Complex myths and magic allow for symbolic and practical ways to organize bodily based emotional experiences and social action, stemming from internal urges, affects and insights. Luc de Heusch’s structural anthropology identifies four main religious ideologies – possession, shamanism, mediunism and prophetism – that share specific relationships to these bodily, mental and social experiences. They can be commented upon as the products of the analogic, affective and imaginative social brain and human theory of mind, that shaped important aspects of cultural ideation and practices impacting on individual, social and ecological contexts of cultural mentalities’ evolution.